Compressive and shear force generated in the lumbar spine of female rowers - Morris, F. L.; Smith, R. M.; Payne, W. R.; Galloway, M. A.; Wark, J. D. (International Journal of Sports Medicine, 2000)
Rowers have and accrue greater lumbar spine bone mineral density (BMD) associated with mechanical loading produced during rowing. The aim of this study was to estimate the mechanical loading generated at the lumbar spine (LS) that is apparently providing an osteogenic benefit. The cohort comprised 14 female rowers (average age: 19.7yrs; height: 170.9 cm, weight: 59.5 kg) and 14 female matched controls (average age: 20.9 m yrs; height: 167.5 cm; weight: 58.1 kg). BMD was assessed using the Hologic QDR 2000+ bone densitometer, indicating higher lumbar spine BMD in the rowers compared to the control subjects (1,069 +/- 0.1 vs. 1,027 +/- 0.1 g/cm2). No significant difference existed for BMD at any other site. All rowers performed a six-minute simulated race on a Concept II rowing ergometer. Mechanical loading generated at the lumbar spine during this task was assessed using a two-dimensional model of the spine, enabling the calculation of the compressive and shear forces at L4/L5. The shear force was the joint reaction force perpendicular to the spine at the L4/L5 joint. Peak compressive and shear force at the lumbar spine of the rowers were 2,694 +/- 609 (N) and 660 +/- 117 (N), respectively. Peak compressive force at the LS relative to body weight was 4.6 times body weight. The literature would suggest that forces of this magnitude, generated at the LS during maximal rowing, may be contributing to the site specific higher LS BMD found in the rowers.